FORMULASI SEDIAAN KRIM EKSTRAK ETANOL DAUN TEH HIJAU (Camellia Sinensis L.) SEBAGAI PELINDUNG SINAR ULTRA VIOLET - Dadih Supriadi (JURNAL FARMASI GALENIKA, 2014)
Green tea (Camellia Sinensis L.) is known to have several pharmacological activities of which are antioxidants. This research aims to make preparations cream formula ethanol extract of green tea leaves as a protection against ultraviolet light exposure. Cream made using the material forming wax cream fan sew-p 10%. Organoleptic testing cream preparation includes observation of discoloration, odor, pH, and homogeneity during storage. The organoleptic evaluation of preparation has been done includes observation of changes in color, odor, pH, and homogeneity during storage. Based on the results showed that ultraviolet light protective cream with dosage of extract concentration of 2%, 4%, 6%, and 8% stable during storage. Viscosity evaluation showed an increase in viscosity during 28 days of observation. The results of effectiveness evaluation with ultraviolet spectrophotometric method showed that increasing concentration of green tea leaf extract in the preparation can increase the value of SPF (Sun Protector Factor). The value of SPF were 2.32 for 2% extract; 5.09 for 4% extract; 6.71 for 6% extract; 7.48 for 8% extract. From these results, it can be concluded that the formula contained 2%, 4%, 6% and 8% extract as a protective of ultraviolet light.